Shocks at large banks and banking sector distress: the Banking Granular Residual - Sven Blank; Claudia M. Buch; Katja Neugebauer (Deutsche Bundesbank, 2009)
Size matters in banking. In this paper, we explore whether shocks originating at large banks affect the probability of distress of smaller banks and thus the stability of the banking system. Our analysis proceeds in two steps. In a first step, we follow Gabaix (2008a) and construct a measure of idiosyncratic shocks at large banks, the so-called Banking Granular Residual. This measure documents the importance of size effects for the German banking system. In a second step, we incorporate this measure of idiosyncratic shocks at large banks into an integrated stress-testing model for the German banking system following De Graeve et al. (2007). We find that positive shocks at large banks reduce the probability of distress of small banks.
Keywords: E44; E52; E32; G21; 330; Banking sector distress; size effects; shock propagation; Granular Residual; Großbank; Schock; Ansteckungseffekt; Bankrisiko; Bankenkrise; Bankensystem; Deutschland